Longevity and technological change - Agnieszka Gehringer; Klaus Prettner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We analyze the impact of increasing longevity on technological progress within a simple R&D-based growth framework with overlapping generations and test the model's implication on OECD data from 1960 to 2011. The central hypothesis derived in the theoretical part is that - by raising the incentives of households to invest in physical capital and in R&D - decreasing mortality positively impacts upon technological progress and productivity growth. The empirical results clearly confirm the theoretical prediction. This implies that the demographic changes we observed in industrialized economies over the last decades were not detrimental to economic prosperity, at least as far as technological progress and productivity growth are concerned.
Keywords: J11; O11; O41; 330